Reporte de dos plantas hospederas de Agrosoma pulchella (Guérin-Méneville, 1829) y Cladonota apicalis (Stal, 1869) en México - Romero Nápoles, Jesús; Castro-Valderrama, Ulises (Instituto de Ecología, A.C., 2018)
In a short stay in 2017 at the Reserva de la Biosfera Los Tuxtlas, there were made some biological observations about a couple of insect species, with those we were able to discover its host plants. After taxonomic determination of both plants and insects there were found that Agrosoma pulchella (Guérin-Méneville, 1829) uses as host plant Plectranthus amboinicus (Lour.) Spreng. and Cladonota apicalis (Stal, 1869) uses Piper hispidum Sw. Moreover, and the distribution for both insect species is given.